Determinants of internationalisation through strategic alliances: Insights based on new data on large Finnish firms - Christopher Palmberg; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2005)
The internationalisation of firms is a salient feature of ongoing globalisation. Internationalisation has traditionally occurred through the extensions of the in-house activities of firms through foreign direct investments or other equity-based arrangements. However, the recent rapid growth of cross-border strategic alliances indicates that such international alliances increasingly complement in-house activities. Nowadays international alliances are typically based on looser non-equity agreements between firms in activities ranging from joint R&D, production, or various market-related activities. In this study we draw on new data to identify the determinants of nonequity international alliance formation of large Finnish firms and thereby contribute with new insights into the reasons behind the recent internationalisation of these firms through strategic alliances. The econometric analysis is framed in terms of organisational theories of the firm, which emphasise the relationships between uncertainties embedded in the activities undertaken within alliances and their organisation. The results suggest that the involvement of firms in uncertain R&Dor market- related activities, and ICT technologies, determine the preference for non-equity alliances over equity-based ones in their internationalisation effort. In contrast, production- related activities are associated with tighter equity-based alliance organisations. Non-equity strategic alliances have thereby contributed less to the internationalisation of production-related activities when compared with R&D and market-related activities. – – Yritysten kansainvälistyminen on oleellinen osa menneillään olevaa globalisaatiokehitystä. Yritykset ovat perinteisesti kansainvälistyneet suorien ulkomaisten investointien kautta. Kansainvälisten strategisten allianssien lukumäärän voimakas kasvu viime vuosina indikoi kuitenkin, että allianssit ovat lisäämässä merkitystään yritysten kansainvälistymisponnisteluissa. Alliansseja muodostetaan liittyen niin t&k-, tuotanto- kuin markkinointitoimintoihinkin. Nykyisin yhä suurempi osa alliansseista perustuu ei-pääomasidonnaisiin järjestelyihin. Tässä tutkimuksessa pyritään selittämään tämäntyyppisen ei-pääomasidonnaisten kansainvälisten allianssien muodostamiseen vaikuttavia tekijöitä hyödyntäen tutkimusta varten luotua uutta suomalaisten suuryritysten allianssitietokantaa. Viimeaikaisessa teoreettisessa kirjallisuudessa on korostettu allianssin toimintaan liittyvien epävarmuuksien merkitystä allianssin organisaatiomuodon valinnassa; epävarmuuden lisääntyessä ei-pääomasidonnaiset allianssit ovat tyypillisempiä. Empiirisen analyysin tulokset tukevat tätä käsitystä, sillä ei-pääomasidonnaiset allianssit ovat analyysien mukaan tyypillisiä silloin, kun niiden toiminta liittyy t&k:hon, markkinointitoimintoihin tai ICT teknologiaan. Sitä vastoin vähemmän epävarmuutta sisältävissä tuotantotoimintaan liittyvissä alliansseissa pääomasidonnaiset allianssijärjestelyt ovat tyypillisempiä ja kansainvälistyminen suhteellisesti vähempää strategisten allianssien näkökulmasta.
Keywords: 330; internationalisation; large Finnish firms; uncertainty; strategic alliances; kansainvälistyminen; suomalaiset suuryritykset; epävarmuus; strategiset allianssit; Globalisierung; Internationale Unternehmenskooperation; Risiko; Finnland